Metal organic complexes as an artificial solid-electrolyte interface with Zn-ion transfer promotion for long-life zinc metal batteries. Issue 48 (6th December 2021) - Mu, Yanlu; Zhou, Tianyi; Zhai, Zhaoyi; Zhang, Shuangbin; Li, Dexing; Chen, Lan; Ge, Guanglu
Abstract : The schematic diagram for the plating/stripping process of Zn. (a) Corrosion, by-products, and Zn dendrites are observed on a bare Zn electrode. (b) The Zn–THBA protective layer endows a dense and dendrite-free plating/stripping morphology.  Abstract : Metal organic complexes as an artificial solid-electrolyte interface (MOC-SEI) have been generated via in situ coordinative polymerization between Zn 2+ and organic ligand molecules. Compared to conventional anodes, the MOC-SEI coated anode significantly prolongs the lifespan from 100 h to 1450 h for the Zn||Zn symmetrical cells and increases the reversible capacity up to 160 mA h g −1 after 1100 cycles for the Zn||V2 O5 full-cells.